Designing and building earthquake warning system with Arduino and web-based SES60 SLP sensor - Edidas Edidas; Rusnardi Rahmat Putra (Bulletin of Electrical Engineering and Informatics, 2022)
Indonesia is a country that is crossed by a world ring of fire that has the potential for earthquakes and tsunamis. An earthquake is an occurrence of shaking the ground due to the sudden release of energy into the earth. Since earthquakes occur within an undetermined period, we need a device to detect earthquake vibrations as early as possible within few seconds and announce real-time warning information on the website. The monitor screen displays a flat, a slightly increasing, the alarm displays a sound "weak earthquake”, "moderate earthquake", "strong earthquake", "very strong earthquake”. When there are no earthquake waves, very small shaking, PGA more than 200 gals, PGA more than 400 gals, PGA more than 600 gals and PGA more than 800 gals respectively. The alarm announces watch out (hati-hati) for moderate earthquake PGA more than 200 gals, caution (waspada) PGA more than 400 gals and ask to evacuate for PGA more than 600 gals. The earthquakes detecting devices are useful in reducing their negative impacts, for instance, fatalities and material losses. The development of this system is to provide faster and more accurate information, and we can access the information on the internet network with broad coverage. The system can send the information within 5 second to user.